2019
DOI: 10.1101/674358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NONU-1 encodes a conserved endonuclease required for mRNA translation surveillance

Abstract: Cellular translation surveillance rescues ribosomes that stall on problematic mRNAs. During translation surveillance, endonucleolytic cleavage of the problematic mRNA is a critical step in rescuing stalled ribosomes. However, the nuclease(s) responsible remain unknown. Here we identify NONU-1 as a novel endoribonuclease required for translation surveillance pathways including No-Go and Nonstop mRNA Decay. We show that: (1) NONU-1 reduces Nonstop and No-Go mRNA levels; (2) NONU-1 contains an Smr RNase domain re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…It has been recently reported that Cue2 is the endonuclease that cleaves NGD/NSD targeted RNAs 36,37 . Its action has been proposed to occur in the ribosome A site and therefore deviates significantly from our observations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that Cue2 is the endonuclease that cleaves NGD/NSD targeted RNAs 36,37 . Its action has been proposed to occur in the ribosome A site and therefore deviates significantly from our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Another important question is whether the mRNA-extracting function of the Ski complex could play a role in the RQT-mediated or any other surveillance and quality control mechanism. Notably, nonstop suppression in a C. elegans skih-2 nonu-1 double mutant was greater than in either single mutant, suggesting that the activities of NONU-1 and the Ski complex may not be strongly interdependent (Glover et al, 2019).…”
Section: A B C D E Fmentioning
confidence: 95%
“…Although endonucleolytic cleavage of mRNA upstream of the stall site is an established hallmark of No-Go decay (Doma and Parker, 2006), the nature of this process has remained obscure. Recent studies showed that ribosomal ubiquitination acts as a signal for recruitment to the stall site of an endonuclease, identified as Cue2 in Saccharomyces cerevisiae (D'Orazio et al, 2019) and NONU-1 in Caenorhabditis elegans (Glover et al, 2019). Cleavage is reported to occur in the A site of collided ribosomes (D'Orazio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In either case, the ribosome stalls after translating to the end of the mRNA. As in no-go decay, removal of the arrested ribosome involves endonucleolytic cleavage of the mRNA and ribosome rescue by PELO and HBS1 (25), and a preliminary report has identified Cue2/N4BP2 as the required endonuclease (29).…”
Section: Cytoplasmic Surveillance Of Protein-coding Transcriptsmentioning
confidence: 99%